Mitochondrial Protein PGAM5 Emerges as a New Regulator in Neurological Diseases - Liang, Min-Zong; Ke, Ting-Ling; Chen, Linyi (Frontiers in Molecular Neuroscience, 2021)
As mitochondrial dysfunction has increasingly been implicated in neurological diseases, much of the investigation focuses on the response of the mitochondria. It appears that mitochondria can respond to external stimuli speedy fast, in seconds. Understanding how mitochondria sense the signal and communicate with cytosolic pathways are key to understand mitochondrial regulation in diseases or in response to trauma. It was not until recently that a novel mitochondrial protein, phosphoglycerate mutase family member 5 (PGAM5) has emerged to be a new regulator of mitochondrial homeostasis. Although controversial results reveal beneficial as well as detrimental roles of PGAM5 in cancers, these findings also suggest PGAM5 may have diverse regulation on cellular physiology. Roles of PGAM5 in neuronal tissues remain to be uncovered. This review discusses current knowledge of PGAM5 in neurological diseases and provides future perspectives.